2019
DOI: 10.7717/peerj.7037
|View full text |Cite
|
Sign up to set email alerts
|

The role of acetyl-coA carboxylase2 in head and neck squamous cell carcinoma

Abstract: Background Acetyl-CoA carboxylase (ACC) plays an important role in the metabolism of various cancer cells, but its role in head and neck squamous cell carcinoma (HNSCC) is uncertain. Therefore, in the present study, we explored the role of ACC2 in HNSCC. Methods Western blot and immunohistochemistry assays were used to determine ACC2 protein expression levels in laryngocarcinoma and adjacent normal tissues derived from patients with laryngocarcinoma. ACC2 expression was knocked down in the hypopharyngeal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…ACC2 protein is highly expressed in laryngocarcinoma, and ACC2 expression level is positively associated with clinical cancer stage and a decreased 5-yr survival rate ( Li et al, 2019a ). During nutrient abundance, prolyl hydroxylase domain protein 3 (PHD3) hydroxylates and activates ACC2, thereby repressing FAO.…”
Section: Lipogenesismentioning
confidence: 99%
“…ACC2 protein is highly expressed in laryngocarcinoma, and ACC2 expression level is positively associated with clinical cancer stage and a decreased 5-yr survival rate ( Li et al, 2019a ). During nutrient abundance, prolyl hydroxylase domain protein 3 (PHD3) hydroxylates and activates ACC2, thereby repressing FAO.…”
Section: Lipogenesismentioning
confidence: 99%
“…The link between the lipid metabolism associated molecules and neoplastic phenotypic changes in HNSCC was initially evident from a finding that caspase-triggered SREBP activation is a key molecular mechanism for HNSCC cell death under CDDP treatment [109]. A number of studies were later conducted to delineate the roles of different lipogenic proteins, including ACCs [110,111,112], FASN [113] and sphinogosine-1-phosphate metabolic enzymes [114], as well as a lipid catabolic factor lipolysis-stimulated lipoprotein receptor (LSR) [115] in controlling the HNSCC malignancy. In general, the molecules involved in lipogenesis are upregulated during HNSCC development and serve as an oncogenic indicator in clinic [110,114,116]; in contrast, lipid catabolic cues display a tumor-suppressive effect in HNSCCs.…”
Section: Development Of Anti-cancer Scheme By Targeting Distinct Mmentioning
confidence: 99%
“…Despite the endeavors in targeting aerobic glycolysis in the treatment of SCCHN, no glycolytic inhibitors have been used in the clinical setting so far [ 12 ], suggesting that SCCHN cells might have alternative metabolic pathways to acquire energy to survive. Our previous study, and a study by another group, have shown that overexpression of phosphorylated inhibitory ACC1 or ACC2 was associated with a decreased survival rate in SCCHN [ 4 , 5 ]. Since the major function of ACC1 is to regulate fatty acid metabolism, and ACC2 regulates FAO [ 13 , 14 ], the reprograming of lipid metabolism may play a role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…One of the hallmarks of SCCHN is the reprogramming of cellular energy metabolism [ 2 , 3 ]. SCCHN tumors expressing a high level of phosphorylated acetyl-CoA carboxylase 1 (pACC1) or ACC2 are associated with decreased survival [ 4 , 5 ]. The major cellular function of ACC is to produce malonyl-CoA from acetyl-CoA for fatty acid synthesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation